2015
DOI: 10.3382/ps/pev069
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance profiles among mesophilic aerobic bacteria in Nigerian chicken litter and associated antibiotic resistance genes

Abstract: The effect of global antibiotic use practices in livestock on the emergence of antibiotic resistant pathogens is poorly understood. There is a paucity of data among African nations, which suffer from high rates of antibiotic resistant infections among the human population. Escherichia (29.5%), Staphylococcus (15.8%), and Proteus (15.79%) were the dominant bacterial genera isolated from chicken litter from four different farms in Zaria, Nigeria, all of which contain human pathogenic members. Escherichia isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
7
18
1
1
Order By: Relevance
“…It was observed in this study that multiple antibiotic resistance was common among E. coli and Salmonella spp. These results are in agreement with previous reports in Nigeria (Raji et al, 2007;Olonitola et al, 2015). There was complete resistance of E. coli and Salmonella to ampicillin, oxacillin, cefuroxime, ceftazidime, erythromycin and sulphamethoxazole/trimethoprim.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was observed in this study that multiple antibiotic resistance was common among E. coli and Salmonella spp. These results are in agreement with previous reports in Nigeria (Raji et al, 2007;Olonitola et al, 2015). There was complete resistance of E. coli and Salmonella to ampicillin, oxacillin, cefuroxime, ceftazidime, erythromycin and sulphamethoxazole/trimethoprim.…”
Section: Discussionsupporting
confidence: 93%
“…Van den Bogaard et al (2001) explained that usage of antibiotics was the most significant factor responsible for antimicrobial resistance in bacteria. This view may also explain the reason for emerging antibiotic resistance in Nigeria, since antibiotics are used excessively in poultry and livestock in Nigeria without regulation (Raji et al, 2007;Geidam et al, 2012;Olonitola et al, 2015). Van den Bogaard et al (2001) further observed that other factors that select for antimicrobial resistance in bacteria include overcrowding and poor sanitation.…”
Section: Discussionmentioning
confidence: 99%
“…This category included 42 studies, with the inclusive eligibility criteria in which diverse phenotypic or genotypic methods were utilized ([14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], Tables S1–S3). These studies sought to detect the presence and extent of AMR in collected samples with a selected panel of antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…The 80 studies excluded did not directly relate to the objectives or yielded information that could be subjected to organized peer review and data analysis. The 59 included studies were sorted into three categories of 42 antimicrobial resistance studies [14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55], 16 antimicrobial residue studies [56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71], and 1 antiseptic or disinfectants study [72]. The PRISMA-style flowchart was modified and used for this analytical review (Figure S1) [73].…”
Section: Methodsmentioning
confidence: 99%
“…The persistent use of antibiotics is suspected to be the major cause of antibiotic resistance in man and animal (Adejoro, 2007). The overall relationship between drug use and resistance is well established and based on laboratory, cross-sectional, case-control and prospective studies (Olonitola et al, 2015). Also, self-medication with antibiotics, use of human antibiotics in food animals and non-regulated prescriptions are increasingly alarming and may have contributed to antibiotic resistance scourge in the poultry industry in Nigeria.…”
Section: Discussionmentioning
confidence: 99%